THE EFFECT OF HEALTH EDUCATION WITH NON-DIGITAL GAMIFICATION METHOD ON FEMALE STUDENTS' KNOWLEDGE ABOUT SEXUAL VIOLENCE PREVENTION AT MADINATUL QUR'AN ISLAMIC BOARDING SCHOOL BOGOR 2026 - Fitrul Khoironi; Darmasta Maulana; Ivana Eko Rusdiatin; Arni Wianti (International Journal of Multidisciplinary Research and Literature, 2026)
Sexual violence against adolescent girls remains a public health problem that requires preventive measures through effective and culturally appropriate health education. Islamic boarding schools (pesantren) have limitations in discussing sexuality issues, requiring interactive educational methods that align with Islamic values. This study aims to determine the effect of health education using non-digital gamification methods (card games) on female students' knowledge of sexual violence prevention at Madinatul Qur'an Islamic Boarding School in Bogor in 2026. This study used a quasi-experimental design with a pre-test post-test control group design approach. The study sample consisted of 44 female junior high school students divided into an experimental group and a control group of 22 respondents each using a purposive sampling technique. The research instrument used a questionnaire on knowledge of sexual violence prevention. Data analysis was performed using the Wilcoxon test. The results showed that in the experimental group there was an increase in knowledge with a significance value of p = 0.000 (p <0.05), while the control group obtained a value of p = 0.058 (p>0.05). These results indicate that health education using non-digital gamification methods significantly improved female students' knowledge of sexual violence prevention. This method is effective as an interactive, participatory health education medium, and is appropriate for the Islamic boarding school environment.